Governance in Transitional Societies in East and Southeast Asia - Zhang, Chi; Trinh, Binh Thi An (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
XI, 173 p. 8 illus., 7 illus. in color.